A comparative study of bearing capacity of shallow footing under different loading conditions. Issue 4 (4th July 2022) - Gupta, Sujata; Mital, Anupam
ABSTRACT: In the present study, the behaviour of a shallow rectangular foundation placed over the multiple layers of the geogrid reinforced sand under eccentric and oblique loads in both dimensions was studied. Various parameters were investigated in this study including the number of reinforced layers ( N ), eccentricity ( e/B, e/L ) and inclination of applied load ( α ). Bi-axial geogrid (Bx20/20)-reinforced sand and laboratory results were compared with PLAXIS 3D software keeping N, eccentricity ratios and angle of inclination as input parameters. The results present that the value of Ultimate Bearing Capacity (UBC) of model foundation found reduced as the axial eccentricity and inclination of applied loads increased. It also found that multiple geogrid-reinforced layers increased the UBC of about 75%. Finally, the model test results were analysed using PLAXIS 3D. A good agreement was originated between the laboratory results and numerical analysis.